Differentiated Learning Practices and Fifth Grade Social Skills Development: Praktik Pembelajaran Berdiferensiasi dan Pengembangan Keterampilan Sosial Siswa Kelas Lima - Muhammad Dimas Rahmadani; Tri Linggo Wati (Academia Open, 2025)
General Background: Elementary education under the Independent Curriculum promotes student-centered instruction that integrates academic achievement with social competence. Specific Background: Differentiated learning offers adaptive strategies by adjusting content, process, and product to diverse learner characteristics in heterogeneous classrooms. Knowledge Gap: Although differentiated practices are widely implemented, limited studies examine how the learning process dimension relates to elementary students’ social skills in authentic classroom contexts. Aims: This study analyzes fifth-grade students’ social skills within the process aspect of differentiated learning and identifies supporting and constraining factors during its implementation at an elementary school. Results: Using a descriptive qualitative design through observations, interviews, and documentation, findings show teachers applied differentiation mainly in content and product, while students demonstrated progress in empathy, cooperation, responsibility, and emotional regulation. However, inconsistencies in social behavior, unequal task participation, and limited differentiation in learning processes and environments were still observed. Novelty: The research provides a focused examination of social skill indicators derived from the classroom process of differentiated instruction. Implications: The findings highlight the need for more holistic and data-based differentiation practices to foster sustainable interpersonal growth and inclusive classroom interaction. Keywords: Differentiated Learning, Social Skills, Elementary Students, Learning Process, Independent Curriculum Key Findings Highlights: Students displayed stronger empathy and peer collaboration Flexible task options encouraged responsibility and engagement Process dimension required broader classroom application